Phase II INTERACT-ION study: ezabenlimab (BI 754091) and mDCF (docetaxel, cisplatin, and 5-fluorouracil) followed by chemoradiotherapy in patients with Stage III squamous cell anal carcinoma - Kim, Stefano; Boustani, Jihane; Vernerey, Dewi; Vendrely, Véronique; Evesque, Ludovic; Francois, Eric; Quero, Laurent; Ghiringhelli, Francois; de la Fouchardière, Christelle; Dahan, Laëtitia; Bouché, Oliver; Chibaudel, Benoist; et al. (Frontiers in Oncology, 2022)
Background: Chemoradiotherapy alone is the standard treatment for locally advanced squamous cell anal carcinoma (SCAC). However, up to 50% of patients will experience recurrence; thus, there is a need for new treatments to improve outcomes. Modified docetaxel, cisplatin and 5-fluorouracil (mDCF) is a treatment option for first-line metastatic SCAC, having shown efficacy in the Epitopes-HPV01 and -02 trials (NCT01845779 and NCT02402842). mDCF treatment also plays a role in the modulation of anti-tumor immunity, suggesting it may be a good combination partner for immunotherapy in patients with SCAC. Anti-programmed death protein-1 (PD-1) immunotherapy has been shown to be effective in metastatic SCAC. We therefore designed the INTERACT-ION study to assess the combination of mDCF with ezabenlimab (BI 754091), an anti-PD-1 antibody, followed by chemoradiotherapy, in patients with Stage III SCAC. Methods: INTERACT-ION is a pivotal, open-label, single-arm phase II study in patients with treatment-naïve Stage III SCAC. Patients will receive induction treatment with mDCF (docetaxel 40 mg/m2 and cisplatin 40 mg/m2 on Day 1, 5-fluorouracil 1200 mg/m2/day for 2 days) every 2 weeks for 4 cycles and ezabenlimab (240 mg given intravenously) every 3 weeks for 3 cycles. In the absence of disease progression at 2 months, two additional cycles of mDCF and one additional cycle of ezabenlimab will be administered. Patients with radiological objective response, pathological complete/near-complete response and biological complete response will then receive an involved-node radiotherapy with intensity-modulated radiation therapy and concurrent chemotherapy, followed by ezabenlimab alone for seven cycles. All other patients will receive standard chemoradiotherapy. The primary endpoint is the clinical complete response rate 10 months after the first cycle of mDCF plus ezabenlimab. Major secondary endpoints are major pathological response and biological complete response after induction treatment. An extensive ancillary biomarker study in tumor tissue and peripheral blood will also be conducted. Discussion: The addition of immunotherapy to chemotherapy is an area of active interest in metastatic anal cancer. This pivotal study will evaluate this combination in the locally advanced setting. Ancillary biomarker studies will contribute to the understanding of predictors of response or resistance to treatment. Trial registration number: NCT04719988